Targeted Mutation (R100W) of the Gene Encoding NGF Leads to Deficits in the Peripheral Sensory Nervous System - Yang, Wanlin; Sung, Kijung; Zhou, Fengli; Xu, Wei; Rissman, Robert A.; Ding, Jianqing; Wu, Chengbiao (Frontiers in Aging Neuroscience, 2018)
Nerve growth factor (NGF) exerts multifaceted functions through different stages of life. A missense mutation (R100W) in the beta-NGF gene was found in hereditary sensory autonomic neuropathy V (HSAN V) patients with severe loss of pain perception but without overt cognitive impairment. To better understand the pathogenesis of HSAN V, we generated the first NGFR100W knock in mouse model for HSAN V. We found that the homozygous exhibited a postnatal lethal phenotype. A majority of homozygous pups died within the first week. Some homozygous pups could ingest more milk and survived up to 2 months by reducing litter size. Whole mount in situ hybridization using E10.5 embryos revealed that, compared to wild type, R100W mutation did not alter the gene expression patterns of TrkA and P75NTR in the homozygous. We also found that the homozygotes displayed normal embryonic development of major organs (heart, lung, liver, kidney and spleen). Furthermore, the homozygotes exhibited severe loss of PGP9.5-positive intra-epidermal sensory fibers. Taken together, our results suggest that, as with HSAN V patients, the R100W mutation primarily affects the peripheral sensory nervous system in the mouse model. This novel mouse model makes it possible to further study in vivo how NGFR100W uncouple trophic function from nociception of NGF.